1995
DOI: 10.1111/j.1540-8159.1995.tb04743.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Saline Infusion Electrode Catheter for Improved Energy Delivery and Increased Lesion Size in Radiofrequency Catheter Ablation

Abstract: Although radiofrequency catheter ablation has undergone explosive growth as the treatment for a variety of arrhythmias, a limiting factor with the existing catheter delivery system has been the relatively small size of the lesions, which appears to be in part due to coagulum formation around the catheter tip, producing a rise in impedance and limiting energy delivery. In order to test the hypothesis that infusion of saline during radiofrequency current application can increase the lesion size and decrease the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…
saline into the tissue through the hollow electrode tip Purpose: To investigate whether radiofrequency [6][7][8]. The conductivity of normal saline is 3 to 5 times (RF) therapy with hypertonic saline infusion through higher than that of the blood and 12 to 15 times higher a hollow screw-tip electrode can cause a lesion size than that of tissues.
…”
mentioning
confidence: 99%
“…
saline into the tissue through the hollow electrode tip Purpose: To investigate whether radiofrequency [6][7][8]. The conductivity of normal saline is 3 to 5 times (RF) therapy with hypertonic saline infusion through higher than that of the blood and 12 to 15 times higher a hollow screw-tip electrode can cause a lesion size than that of tissues.
…”
mentioning
confidence: 99%
“…17) To the best of our knowledge, only one previous study has presented subacute phase lesion dimensions at 4-7 days after RF ablation by saline irrigated catheter. 18) However, no previous study has compared acute and chronic phase lesion dimensions. Study limitations: This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of early success rates with previous studies 12,13 is difficult because success is often reported as the ablation of a "targeted" or "clinical" VT, without regard to the presence of other inducible VTs. The efficacy of standard RF was similar to that observed in a previous study of 52 patients from our group.…”
Section: Discussionmentioning
confidence: 99%